Penyuluhan Kesehatan Tentang Diabetes Mellitus Di Puskesmas Bintuhan Desa Sinar Pagi Kelurahan Bandar Kecamatan Kaur Selatan Kabupaten Kaur - Putri, Mike Milo Diana; Noviza; Sari, Dewi Putri Kemala; Dian Pratiwi; Yeka Hermalen; Lestari, Emi Kasih; Septinawati; Handayani, Seventri Herma; Ferry Surahman; Tuti Rohani; Sari, Fikitri Marya (Utami Publisher, 2025)
Diabetes Mellitus (DM) is a disease that has recently become more common. We also often refer to diabetes mellitus as diabetes or blood sugar disease. This disease is a type of chronic disease whose initial sign is an increase in blood sugar levels as a result of a disturbance in the body's metabolic system. The body organ that is disturbed is the pancreas, which no longer functions as it should. The pancreas is no longer able to produce the hormone insulin to meet the body's needs.One of the factors that influence diabetes mellitus is a lack of knowledge. Public knowledge about diabetes mellitus is very much needed as a foundation for society in demonstrating diabetes mellitus prevention behavior. Knowledge is very important for the formation of behavior (Donsu, 2017). Knowledge is also related to the level of education. The higher a person's level of education, the more information they will have, which will influence a person's behavior (Notoatmodjo, 2002). One alternative for dealing with diabetes mellitus is to do diabetes mellitus exercises. Objective: At the end of the counseling process, all elderly and pre-elderly people in Sinar Pagi Village will be able to understand and understand Diabetes Mellitus and participate in doing diabetes mellitus exercises. Method: The method used in providing education about diabetes mellitus is lectures and questions and answers as well as distributing leaflets. Then the diabetes mellitus exercise method used is direct practice of diabetes mellitus exercises. Results and Discussion: In this outreach activity, the elderly experienced an increase in knowledge from the pre-test with an average of 65 and post-test with an average of 80, with a difference of 15. The final results of this diabetes mellitus exercise activity made the cadres agree to Do diabetes mellitus exercises for the elderly at least 1-2 times every month.